Pojmovanje vzgoje v slovenski duhoslovni pedagogiki po prvi svetovni vojni - Šmidhofer, Ana (Revija za elementarno izobraževanje, 2018)
The Concept of Education in Slovene Cultural Pedagogy after the First World War. The discussion analyses the concept of education in Slovene cultural pedagogy after the First World War and shows how education was understood by the leading representatives of this pedagogical orientation: Karel Ozvald, Franjo Čibej, and Stanko Gogala. At the outset, we outline the fundamental characteristics of cultural pedagogy in Germany, from which this pedagogical direction emerges. We then present the essential features of  Slovene cultural pedagogy. The core of the discussion analyses the understanding of education (and related phenomena) at Ozvald, Čibej, and Gogala. In the conclusion we indicate the position of this pedagogical orientation in the second half of the 20th century and its topicality from the point of view of contemporary pedagogy.  DOI: 10.18690/1855-4431.11.1.91-108(2018)COBISS-ID: 23817480
Keywords: cultural pedagogy; hystory of pedagogy (1920−1940); education; Slovenia; contemporary pedagogy